Hubungan Antara Spiritualitas dengan Tingkat Stres pada Lansia di Rumah Pelayanan Sosial Lanjut Usia Pucanggading Semarang dan Wening Wardoyo Ungaran - Jesica Sari Dea Saputri; Iskim Luthfa; Aspihan Aspihan (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Elderly is the end of the human life process which causes decreased activity. The stress that arises during the aging process can cause three types of changes, namely changes in self-perception, changes in relationships with other people, and philosophical changes regarding priorities, perseverance, and spirituality. Apart from that, spirituality can also help someone develop their awareness. Stress can be avoided if a person has a high level of spirituality, spirituality can be understood as a relationship between a person and God. The aim of this research is to determine the relationship between spirituality and the stress level of elderly people in Social Service Homes. This study used a cross-sectional design. The sample in this study was 105 respondents using purposive sampling. Spirituality data was collected using the SAS questionnaire and Stress Levels using the DASS questionnaire. This research shows a high level of spirituality of 52.4%, moderate spirituality of 40%, low spirituality of 7.6% and a level of severe stress of 24.8%, a level of moderate stress of 58.1%, a level of light stress of 17.1%.